Wnt10b promotes hair follicles growth and dermal papilla cells proliferation via Wnt/β-Catenin signaling pathway in Rex rabbits. Issue 2 (4th February 2020) - Wu, Zhenyu; Zhu, Yanli; Liu, Hongli; Liu, Gongyan; Li, Fuchang
Abstract: Wnt signaling plays an important role in the growth and development of hair follicles (HFs). Among the signaling molecules, Wnt10b was shown to promote the differentiation of primary skin epithelial cells toward the hair shaft and inner root sheath of the HF cells in mice in vitro . Whisker HFs were isolated from Rex rabbits and cultured in vitro to measure hair shaft growth. Meanwhile, dermal papilla cells (DPCs) were isolated and cultured in vitro . Treatment with AdWnt10b or the Wnt/β-Catenin Pathway inhibitor, XAV939, assessed the DPCs proliferation by CCK-8 assay. And the cell cycle was also analyzed by flow cytometry. We found that Wnt10b could promote elongation of the hair shaft, whereas XAV-939 treatment could eliminated this phenomenon. AdWnt10b treatment promoted the proliferation and induced G1/S transition of DPCs. AdWnt10b stimulation up-regulated β-Catenin protein in DPCs. Inhibition of Wnt/β-Catenin signaling by XAV-939 could decreased the basal and Wnt10b-enhanced proliferation of DPCs. And could also suppress the cell cycle progression in DPCs. In summary, our study demonstrates that Wnt10b could promote HFs growth and proliferation of DPCs via the Wnt/β-Catenin signaling pathway in Rex rabbits.